(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
In the past, Filipinos usually enjoyed refreshing drinks such as their favorite buko juice and samalamig. Milk tea swept all Filipinos’ taste buds from the North to the South. The 27th Milktea House offers different milk tea flavors, and there are three store branches in the Philippines: the Meycauayan Bulacan, Bocaue, and Marilao branches. In this study, 27th Milktea House deals with some problems. The store has a common management problem that Milktea owners face, especially in establishments that offer a variety of customized Milktea preparations. It takes time for the customer to claim their orders. This study aims to answer and give recommendations about the problems encountered by 27th Milktea House in assessing customer satisfaction towards service quality. The researchers want to find out if service quality improves customer satisfaction. They will also be able to use the plan made by the researchers to improve the overall quality of the service. The owner will make use of it in order to enhance and advance the level of service that is provided to the customers. The findings of this study revealed that the majority of respondents are males; age: 21-31 years old; employment status: employed; marital status: single. The assessment of the respondents towards customer satisfaction in terms of discovery, trust, integrity, and judgment was interpreted as Agree. The assessment of the respondents towards service quality in terms of tangibility, reliability, responsiveness, and assurance was also interpreted as agreeable. The results of this study revealed that there is a significant relationship between customer satisfaction and service quality. This study suggested that the business must explore and enhance its strategies in increasing customer satisfaction towards service quality. The researchers suggest their proposed improved service quality plan to be used by the management to increase customer satisfaction and to attract more customers. Keywords: Business Administration